2016
DOI: 10.1186/s40064-016-3480-y
|View full text |Cite
|
Sign up to set email alerts
|

A nature-based approach for managing the invasive weed species Gutenbergia cordifolia for sustainable rangeland management

Abstract: BackgroundThe invasive weed species Gutenbergia cordifolia has been observed to suppress native plants and to dominate more than half of the entire crater floor (250 km2) in the Ngorongoro Conservation Area (NCA). As this species has been found to be toxic to ruminants it might strongly impact animal populations in this ecologically diverse ecosystem. Hence, a nature-based approach is urgently needed to manage its spread. We tested two Desmodium spp extracts applied to G. cordifolia and assessed the latter’s g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…A total of 10203 patients diagnosed with various cancers, including laryngeal squamous cell carcinoma (LSCC) [ 22 ], ovarian cancer (OC) [ 23 ], renal cell carcinoma (RCC) [ 24 ], non-small cell lung cancer (NSCLC) [ 25 ], pancreatic cancer (PC) [ 26 29 ], colorectal cancer (CRC) [ 30 – 33 ], nasopharyngeal cancer (NPC) [ 21 , 34 36 ], gastric cancer (GC) [ 37 , 42 ], oral squamous cell carcinoma (OSCC) [ 38 ], hepatocellular carcinoma (HCC) [ 39 , 43 ], esophageal squamous cell carcinoma (ESCC) [ 40 , 41 ], small cell lung cancer (SCLC) [ 44 ], were included. These studies originated from China [ 21 24 , 27 , 28 , 33 – 36 , 39 – 42 , 44 ], Japan [ 26 , 30 32 , 37 , 43 ], and Korea [ 25 , 29 , 38 ], respectively. Twenty-three articles reported the outcomes of overall survival (OS) [ 21 31 , 33 – 44 ], and 6 studies presented disease free survival (DFS) as survival endpoint [ 22 , 24 , 26 , 32 , 34 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 10203 patients diagnosed with various cancers, including laryngeal squamous cell carcinoma (LSCC) [ 22 ], ovarian cancer (OC) [ 23 ], renal cell carcinoma (RCC) [ 24 ], non-small cell lung cancer (NSCLC) [ 25 ], pancreatic cancer (PC) [ 26 29 ], colorectal cancer (CRC) [ 30 – 33 ], nasopharyngeal cancer (NPC) [ 21 , 34 36 ], gastric cancer (GC) [ 37 , 42 ], oral squamous cell carcinoma (OSCC) [ 38 ], hepatocellular carcinoma (HCC) [ 39 , 43 ], esophageal squamous cell carcinoma (ESCC) [ 40 , 41 ], small cell lung cancer (SCLC) [ 44 ], were included. These studies originated from China [ 21 24 , 27 , 28 , 33 – 36 , 39 – 42 , 44 ], Japan [ 26 , 30 32 , 37 , 43 ], and Korea [ 25 , 29 , 38 ], respectively. Twenty-three articles reported the outcomes of overall survival (OS) [ 21 31 , 33 – 44 ], and 6 studies presented disease free survival (DFS) as survival endpoint [ 22 , 24 , 26 , 32 , 34 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies included cancer patients with all disease stages (Stage I–IV or limited-extensive stage) [ 22 26 , 28 31 , 34 36 , 38 , 39 , 41 , 43 , 44 ], three studies recruited patients with Stage I–III [ 37 , 40 , 42 ], and four studies reported advanced stages (III, IV, or III-IV) [ 21 , 27 , 32 , 33 ]. The primary treatments were extremely various among these 24 included studies, including surgery [ 22 24 , 26 , 31 , 37 43 ], chemotherapy (CT) [ 21 , 25 , 27 , 29 , 30 , 32 , 33 , 44 ], and concurrent chemoradiotherapy (CCRT) [ 34 36 ]. The hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) of these 24 studies were all directly extracted from the outcomes of multivariate analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Biological invasions occur when species are introduced into new habitats (Qasem and Foy 2001;Hejda et al 2009;Ngondya et al 2016b;Ellison and Cock 2017;Pratt et al 2017). Species introduction threatens biological conservation, ecosystems services, species diversity and food security (Ellison and Cock 2017;Pratt et al 2017;Witt et al, 2018;Bajwa et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic herbicides are often broad-spectrum and would thus have deleterious non-target effects on native, threatened or ecologically valuable plant species (Ngondya et al 2016b;Ellison and Cock 2017). They can have lethal or sub-lethal impacts on beneficial invertebrates such as insect natural enemies, pollinators (Balbuena et al 2015), and decomposers, as well as soil macrobes and microbes, which play a vital role in nutrient cycling (Frimpong et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation